Whose Literacy Learning Landscapes Matter? Learning From Children’s Disruptions (LEARNing Landscapes, 2009)
This article focuses on my shifting concepts of literacy, re-researching and re-positioning about multiple literacies over decades of working with bilingual and multilingual children in diverse language contexts. I use the metaphor children’s disruptions as entry points in establishing cultural dialogues about children’s literacy accomplishments in multilingual contexts. Disruptions refer to children who along the way by a casual utterance, question, informal text or drawing unsettled my thinking about how languages and literacies impact on their identity, cultural positioning and ideological affiliations in different discursive spaces and diasporan communities.
Keywords: literacy; multiple literacies; bilingual; multilingual; identity; cultural positioning; ideological affiliation; context; cultural dialogue; children's disruption